Germline mutations and age at onset of lung adenocarcinoma - Reckamp, KL (2021)
Background: To identify additional at-risk groups for lung cancer screening, which targets persons with a long history of smoking and thereby misses younger or nonsmoking cases, the authors evaluated germline pathogenic variants (PVs) in patients with lung adenocarcinoma for an association with an accelerated onset. Methods: The authors assembled a retrospective cohort (1999-2018) of oncogenetic clinic patients with lung adenocarcinoma. Eligibility required a family history of cancer, data on smoking, and a germline biospecimen to screen via a multigene panel. Germline PVs (TP53/EGFR, BRCA2, other Fanconi anemia [FA] pathway genes, and non-FA DNA repair genes) were interrogated for associations with the age at diagnosis via an accelerated failure time model. Results: Subjects (n = 187; age, 28-89 years; female, 72.7%; Hispanic, 11.8%) included smokers (minimum of 5 pack-years; n = 65) and nonsmokers (lighter ever smokers [n = 18] and never smokers [n = 104]). Overall, 26.7% of the subjects carried 1 to 2 germline PVs: TP53 (n = 5), EGFR (n = 2), BRCA2 (n = 6), another FA gene (n = 11), or another DNA repair gene (n = 28). After adjustment for smoking, sex, and ethnicity, the diagnosis of lung adenocarcinoma was accelerated 12.2 years (95% confidence interval [CI], 2.5-20.6 years) by BRCA2 PVs, 9.0 years (95% CI, 0.5-16.5 years) by TP53/EGFR PVs, and 6.1 years (95% CI, -1.0 to 12.6 years) by PVs in other FA genes. PVs in other DNA repair genes showed no association. Germline associations did not vary by smoking. Conclusions: Among lung adenocarcinoma cases, germline PVs (TP53, EGFR, BRCA2, and possibly other FA genes) may be associated with an earlier onset. With further study, the criteria for lung cancer screening may need to include carriers of high-risk PVs, and findings could influence precision therapy and reduce lung cancer mortality by earlier stage diagnosis.